Analisis Konsep Fisika dalam Teknologi Penggilingan Beras dan Jagung - Putri, Cindy Asa; Fitriyah, Fitriyah; Sudarti, Sudarti; Mahmud, Kendid (Peneliti.net, 2025)
Rice and corn milling represent essential processes in enhancing the economic value of agricultural products through the application of physics-based design principles. This study investigates the integration of key physical concepts—such as mechanical forces, torque transmission, material wear, kinetic energy, and energy efficiency—in milling technologies. Comparative analysis of rice milling machines (hammer mill, disc mill, herb grinder) revealed significant variations in flour characteristics, including bulk density, whiteness, elasticity modulus, and water absorption​ In corn milling, the adoption of Pahl and Beitz's systematic design approach produced machines with optimized structural performance for flour and feed production​. The incorporation of magnetic traps within rice mill hoppers further enhanced output quality by mitigating contamination-induced damage​. These findings underscore the critical role of physics-informed engineering in advancing milling performance, ensuring consistent product quality, and prolonging machine operational life.